Effects of Osimertinib Combined With Pulmonary Rehabilitation and Health Care Training on Pulmonary Function, Complications, and Quality of Life in Patients After Radical Resection of Lung Cancer - Xu, Haijiang; Guo, Ruixia; Yang, Yantao (Frontiers in Public Health, 2022)
Objective To explore the effects of osimertinib combined with pulmonary rehabilitation and health care training on pulmonary function, complications, and the quality of life (QOL) in patients after radical resection of lung cancer. Methods The data of 120 patients with radical resection of lung cancer admitted to The First Affiliated Hospital of Zhengzhou University from February 2020 to February 2021 were retrospectively analyzed. According to the order of admission, they were equally divided into group p and group q. All patients were given pulmonary rehabilitation and health care training, and group p was treated with osimertinib, while group q received the treatment of pemetrexed combined with cisplatin. The pulmonary function, the incidence of complications, and QOL between the two groups were compared. Results Compared with group q, the pulmonary function was higher (P < 0.001), the incidence of complications was significantly lower (P < 0.05), and QOL scores were markedly higher in group p after treatment (P < 0.001). Conclusion The combination of osimertinib and pulmonary rehabilitation and health care training can improve the pulmonary function of patients with non-small cell lung cancer (NSCLC) with radical resection of lung cancer, and reduce their postoperative morbidity, thereby improving their QOL, which is conducive to reducing the patient's and society's medical burden.